199 - HOSPITAL INFECTION AS PERCEIVED BY THE ACCOMPANYING PERSON OF A HOSPITALIZED CHILD (Fiep Bulletin - online, 2011)
This is a case study carried out in a pediatric teaching hospital aimed at analyzing the knowledge of an accompanying person about hospital infection, given that it plays a direct role in child care, even though an absence of an educational practice promoting qualified care can be observed. Data collection used the focus group technique with persons accompanying hospitalized children in March 2008. The results identified were: insufficient knowledge on the part of the accompanying person; failure to transmit information about institutional norms and routines and little sharing by the professionals of the child's health condition and of information about preventing and controlling infection. Thus, a critical reflection must be made on the co-participation of family members in care and on the role of the professional in sharing not only tasks, but mainly, knowledge about humanized care, achieved by adopting permanent health education protocols.
Keywords: hospital infection; child; family